Common challenge topics in pediatric transplantation (Clinics, 2014)
This special issue is dedicated to the common challenge topics in pediatric transplantation. It contains 11 chapters, ranging from clinical research in pediatric transplantation to translational research (from bench to bedside). It includes comprehensive reviews from renowned scientists, clinicians and surgeons from five countries from the International Pediatric Transplantation Association (IPTA), Harvard University, the University of Miami and the University of São Paulo Medical School. The clinical management of specific issues, such as sensitized patients and ABO blood type-incompatible transplantation, is addressed. In addition, the challenges facing this patient population and the future perspectives for clinical research are discussed.